ESTABLISHMENT AND ACTIVITIES OF THE INTERNATIONAL CRIMINAL COURT: CHALLENGE FOR XXI CENTURY - Grasis, Jānis (Administrative and Criminal Justice, 2015)
Without any doubts, we have to recognize that the establishment of International Criminal Court (ICC) is positive step in international humanitarian and criminal law, in order to call to account persons, who has committed the most serious war crimes, crimes against humanity or genocide. The authority of the ICC internationally reduces the fact that United States of America and Russian Federation have not become member states of the ICC. The brief analysis of the court practice of the ICC proves that ICC acts according to the rule of law, taking into account its independent status. In order to improve legal proceedings of the ICC, we have to find innovative mechanisms in cooperation with bodies and institutions of the United Nations Organization, to push the Member states of the United Nations Organization to actively cooperate with ICC; for example – to execute orders of the arrest of the accused persons. The special treatment must be in cases, when Heads of the State has been accused.